IMPROVING STUDENTS' READING COMPREHENSION ABILITY THROUGH THE SQ3R METHOD (SURVEY, QUESTION, READ, RECITE, AND REVIEW) IN INDONESIAN LANGUAGE LESSONS FOR FOURTH GRADE AT SDN 1 LIMBOTO, GORONTALO REGENCY - Nur Anisa Abbas; Lia Nurhayati; Yusraningsih H. Pongoliu (Journal of Education and Teaching Learning, 2026)
This study aims to improve students' reading comprehension skills through the application of Survey, Question, Read, Recite, and Review (SQ3R) method in the Indonesian language class for fourth-grade students at SDN 1 LIMBOTO, GORONTALO REGENCY. This study was motivated by students’ low reading comprehension skills, as evidenced by their difficulty in understanding the content of the text, identifying the main idea, answering questions based on the text, and summarizing the reading. The research design used was Classroom Action Research (CAR) based on the Kemmis and McTagart model, conducted over two cycles. The research subjects consisted of 29 fourth-grade students at SDN 1 LIMBOTO. Data collection techniques included observation, testing, and documentation. The results showed that the application of the SQ3R method was able to improve students' reading comprehension skills. This was evident from the improvement in student learning outcomes in each cycle as well as the increased activity of both teachers and students in the learning process. The SQ3R method helps students become more active in understanding reading materials through activities such az analyzing, formulating questions, active reading, restating the content of the text, and reviewing the material. Thus, the SQ3R method is effective for improving students' reading comprehension skills in Indonesian Language classes at elementary school level.